Towards a theory of the small firm : theoretical aspects and some policy implications - Di Tommaso, Marco R. (ECLAC SantiagoCL, 2000)
Summarizes the main theories of the firm and discusses the limitations. Analyzes the relationship between efficiency and firm size. Defines the concepts and the analytical tools needed for the construction of a theory of the small firm. Examines the technical and productive as well as the social and organisational aspects of the firm.